Unique Multidisciplinary Training Practices in Cytopathology: Simulation Training in Ultrasound-Guided Fine Needle Aspiration of the Thyroid. (18th September 2020) - Ciolino, Allison L.; Anderson, Scott R.; Gibson, Pamela C.; Gilbert, Matthew P.
The training of ultrasound-guided fine needle aspiration in pathology residency and fellowship programs can be a challenging task with variable outcomes, particularly when there is a lack of a standardized approach. In 2014, the Department of Pathology and Laboratory Medicine in collaboration with the Endocrine Division of the Department of Medicine at the University of Vermont Medical Center implemented simulation training for the incoming cytopathology and endocrinology fellows prior to fellows interacting with patients at the clinic in order to provide a structured approach to learning the technical components of ultrasound-guided fine needle aspiration. In 2018, a second simulation session was added to focus on communication, providing fellows an opportunity to further develop the communication skills that enhance patient connection, empathy, and trust. The combined simulation experience has provided the fellows an ideal learning environment to enhance their understanding of the technical aspects of ultrasound-guided fine needle aspiration as well as the necessary components of communication prior to having to perform the procedure on actual patients. This results in a biopsy clinic that runs more efficiently with improved patient satisfaction and trainee confidence when addressing patient concerns. This collaborative training experience also addresses many of the important aspects surrounding the Accreditation Council for Graduate Medical Education competencies in patient safety, procedure, communication, professionalism, and team-based systems. We report the details of these simulation sessions, how they are structured, key stakeholders involved, and means for communicating feedback to our learners with an emphasis on the importance and value of utilizing standardized patients.